Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 4 - Section 4.1 - Integer Exponents and Scientific Notation - 4.1 Exercises: 58

Answer

$-\frac{4}{9}$

Work Step by Step

According to the negative exponent rule, $a^{-n}=\frac{1}{a^{n}}$. Therefore, $-3^{-1}-9^{-1}=-(3^{-1}+9^{-1})=-(\frac{1}{3}+\frac{1}{9})=-(\frac{1\times3}{3\times3}+\frac{1}{9})=-(\frac{3+1}{9})=-(\frac{3+1}{9})=-\frac{4}{9}$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.